1999
DOI: 10.1046/j.1365-2893.1999.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C antibody detection in dried blood spots

Abstract: In the UK, there have been few studies of the seroprevalence of antibodies to hepatitis C virus (anti-HCV). As part of an ongoing prevalence study of HCV in injecting drug users, we have developed a technique for detecting anti-HCV in blood spots dried on filter paper using a commercially available assay. Subjects with and without serum anti-HCV were studied. The manufacturer's recommended cut-off (CO) for a positive anti-HCV result is kit-dependent, and therefore a ratio of test result (T) to kit CO was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 12 publications
4
33
2
1
Order By: Relevance
“…Previous studies have found higher sensitivity for anti-HCV in Salivette samples taken from patients with HCV RNA in serum and high sensitivity and specificity for HCV RNA detection in dried blood spots [Abe and Konomi, 1998;McCarron et al, 1999]. Unfortunately, HCV RNA testing was not funded for our study, and HCV RNA status was recorded from clinical case notes for only 78 patients in the anti-HCVpositive sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found higher sensitivity for anti-HCV in Salivette samples taken from patients with HCV RNA in serum and high sensitivity and specificity for HCV RNA detection in dried blood spots [Abe and Konomi, 1998;McCarron et al, 1999]. Unfortunately, HCV RNA testing was not funded for our study, and HCV RNA status was recorded from clinical case notes for only 78 patients in the anti-HCVpositive sample.…”
Section: Discussionmentioning
confidence: 99%
“…McCarron et al [1999] used the Monolisa anti-HCV (new antigen) (Sanofi Pasteur, France) and estimated the method's sensitivity as 97% and specificity as 100%, using a sample of 108 HCV clinic attenders and 112 blood donors. Abe and Konomi [1998] detected HCV RNA in all spotted serum samples from eight anti-HCV-positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,[22][23][24][25][26][27][28] However there have been few studies published evaluating the use of DBS for the detection of HCV RNA. 29 …”
Section: Introductionmentioning
confidence: 99%
“…This methodology requires costly devices, such as thermal cyclers and sequencers, and expertise in nucleotide sequence analysis that are available in only few reference centers. Many studies have demonstrated the good performances of blotted blood, serum, or plasma samples in serological and molecular diagnosis of different viral infections, including infection with cytomegalovirus (23), human immunodeficiency virus (HIV) (3,18,19), hepatitis C virus (9,16), measles virus (11,15,17), or rubella virus (14). Dried blood spots are notably cost-effective as a blood sample collection device in epidemiologic field studies in developing countries.…”
mentioning
confidence: 99%